Pelayanan Pengunjung Disabilitas pada Museum Geologi dan Museum Konferensi Asia Afrika di Kota Bandung - Permana, Aa (Tourism Scientific Journal, 2024)
This study is entitled "Disability Visitor Service at the Museum of Geology and Museum of the Asia Africa Conference in the Bandung City". This study seeks to find a discussion of museum services for persons with disabilities that substantively refer to the service quality concept revealed by Zeinthaml in 2006 consisting of (1) Tangibles, (2) Empathy, (3) Responsiveness, (4) Reliable and (5) Assurance, and performed at the Museum of Geology and the Museum of Asia Africa. This research uses a qualitative method approach. A qualitative approach is considered by researchers to be very appropriate in providing a holistic picture of the existing reality data. Data collection was performed using observation techniques, in- depth interviews, and documentation. Data analyzed was using the stages described by Miles and Huberman (1992: 16). Based on research, a conclusion can be drawn that both museums have all aspect studied for disabilities tourists. Broadly speaking, the Museum of Geology already has infrastructure and services that prepared for disabilities tourists, meanwhile the Museum of Asia Africa still has a variety of obstacles and minimal infrastructure will be aimed for disabilities tourists with some rules procedure and condition.